Cardiac Thyroid Hormone Metabolism and Heart Failure. Issue 3 (21st July 2017) - Janssen, Rob; Muller, Alice; Simonides, Warner S.
Abstract : The heart is a principal target of thyroid hormone, and a reduction of cardiac thyroid hormone signaling is thought to play a role in pathological ventricular remodeling and the development of heart failure. Studies in various rodent models of heart disease have identified increased activity of cardiac type III deiodinase as a possible cause of diminished levels and action of thyroid hormone. Recent data indicate novel mechanisms underlying the induction of this thyroid hormone-degrading enzyme in the heart as well as post-transcriptional regulation of its expression by microRNAs. In addition, the relevance of diminished thyroid hormone signaling for cardiac remodeling is suggested to include miRNA-mediated effects on pathological signaling pathways. These and other recent studies are reviewed and discussed in the context of other processes and factors that have been implicated in the reduction of cardiac thyroid hormone signaling in heart failure.